AMERICAN ACCOUNTING ASSOCIATION MEMBERS CONTRIBUTING THEORY QUESTIONS TO THE CPA EXAMINATION STOCKPILING PROJECT. - Backer, Morton; Doak, Lowell C.; Vance, Lawrence L.; Young, Kenneth G.; Meier, Robert A. (The Accounting Review, 1959)
During the year 1958 the Committee on Certified Public Accountants (CPA) Examinations of the American Accounting Association continued to cooperate with the Director of Education, Mr. Wilton T. Anderson and the Board of Examiners of the American Institute of Certified Public Accountants in stockpiling questions in Theory of Accounts for the CPA Examinations. The Committee actively encourages all members of the Association to prepare questions and model answers of the type which the members think should be used in future examinations.